The strategic management of the entitlement process in the employment relationship - Heath, Chip; Knez, Marc; Camerer, Colin F. (Strategic Management Journal, 1993)
Over time, members of organizations develop entitlements—preferences about how they wish to be treated and beliefs about how they should be treated. The formation of entitlements is an important subject for strategy researchers because employees resist changes that violate their perceived entitlements; thus entitlements constrain an organization's ability to adapt quickly in a changing environment. In this paper, we use psychological research to propose a two-part model of entitlements formation: (i) Preference formation makes people likely to resist change because preferences adapt to experience, and thus change imposes painful losses; (ii) Belief formation leads to over-entitlement, and this produces resistance because employees perceive changes to be unfair or unjust. Over-entitlement happens because (a) psychological limitations in judgement and (b) strategic distortions in the character and content of information exchanged in relationships lead employees to perceive their entitlements as richer and more systematic than intended by the organization. Combined, the preference and belief formation processes can produce substantial resistance to change. In stable environments firms may have an incentive to allow entitlements to develop since they enhance employee security and commitment. However, in changing environments, entitlements constrain firms' ability to mobilize resources to meet competitive challenges. After presenting our model of entitlement formation, we use the model to organize and analyze a set of suggestions about how the employment relationship might be managed to avoid problems of entitlement formation, thus enabling firms to adapt more effectively in a dynamic environment.